2014
DOI: 10.1155/2014/986127
|View full text |Cite
|
Sign up to set email alerts
|

Matrilin-2 Is a Widely Distributed Extracellular Matrix Protein and a Potential Biomarker in the Early Stage of Osteoarthritis in Articular Cartilage

Abstract: In this study, we first generated and characterized a polyclonal antibody against unique domain of matrlin-2 and then used this specific antibody to assess the expression pattern of matrilin-2 by immunohistochemistry. We found that marilin-2 is widely distributed in the connective tissues of many mouse tissues including heart, colon, penis, esophagus, lung, kidney, tracheal cartilage, developmental bone, and adult bone. The expression level of matrilin-2 was remarkably increased in the tissues of osteoarthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…The gene with the second largest magnitude of negative association with methylation at birth, PRR5L, has been linked in GWAS to allergic diseases, found downregulated (expression) in osteoarthritis, and differentially methylated in type II diabetes [72][73][74]. The gene with the lowest P value in our EWAS, MATN2 plays a critical role in the differentiation and maintenance of skeletal muscles, peripheral nerves, liver and skin during development and regeneration [75] and is suggested as a potential biomarker in the early stage of osteoarthritis [76].…”
Section: Discussionmentioning
confidence: 99%
“…The gene with the second largest magnitude of negative association with methylation at birth, PRR5L, has been linked in GWAS to allergic diseases, found downregulated (expression) in osteoarthritis, and differentially methylated in type II diabetes [72][73][74]. The gene with the lowest P value in our EWAS, MATN2 plays a critical role in the differentiation and maintenance of skeletal muscles, peripheral nerves, liver and skin during development and regeneration [75] and is suggested as a potential biomarker in the early stage of osteoarthritis [76].…”
Section: Discussionmentioning
confidence: 99%
“…Matrilins appear as oligomeric adaptor proteins and mediate the interaction between collagen fibrils and other ECM components to form supramolecular networks. Among the four family members, matrilin2, a substrate of ADAMTS5, is identified in cartilage and many other types of connective tissue 8 . Currently, it is unknown whether the ADMATS5-matrilin2 axis is involved in the mechanism of valvular calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Matrilin2 is a novel member of filament-forming oligomeric adaptor protein family that is involved in the development and homeostasis of the extracellular matrix network. The levels of soluble matrilin2 are remarkably increased during liver cirrhosis, osteoarthritis and other inflammation-associated diseases 7, 8 . Besides its role in modulating extracellular matrix (ECM) network, matrilin2 induces a pro-inflammatory response in macrophages/microglia via Toll-like receptor (TLR)-mediated signaling pathways 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that Matrilin-2 was mainly expressed in glomerulus, the basement membrane of distal convoluted tubule and renal matrix [8], where was the typical lesion location in DN. Change of glucose metabolism could therefore activate intraand extracellular signaling pathways leading to abnormal ECM accumulation.…”
Section: Discussionmentioning
confidence: 93%
“…Matrilin-2 is the largest member of the Matrilin family that shares von Willebrand factor A (vWFA) domains, epithelial growth factor (EGF) like repeats, and a series of heptad repeats at their C-terminal coiled-coil domain [6,7]. Unlike other family members whose expression is limited to skeletal tissues, Matrilin-2 is found heterogeneously distributed in connective tissues, including kidney [8,9]. It has previously been described that Matrilin-2 can interact with itself and a variety of matrix molecules including type 1 collagen, fibronectin, and laminin and has been postulated to act as an adaptor molecule connecting these molecules with other proteins and proteoglycans within the ECM where it may regulate ECM homeostasis [7,10].…”
Section: Introductionmentioning
confidence: 99%